Kemampuan Menetas Telur Ikan Betok (Anabas testudineus) Bloch Dengan Variasi Suhu Yang Berbeda Di Dalam Akuarium - Mukhlisah; Anny Rimalia; Riduansyah (Fakultas Pertanian UVAYA Banjarmasin, 2023)
Climbing Fish (Anabas testudineus) BLOCH culture is very potencial to be depelop. One of the critical succes factors is the succes of cultivition is the availability of good a seeds in sufficient quantities and sustainable. Temperature is one of the factors that influence the hatch ability of eggs. The experiment used a completly randomized design (CRD) method, consisting of three treatment and three replications. The order of treatment was A 26°C, B 28°C and C 30°C. The result of research for each treatment A, B and C indicate that avarage of hatching rate ware 96,53%, 98,33% and 99,31%. Data analysis uses variance test (ANOVA). The result showed the temperature significantly. Result of water quality measurement at each treatment is pH 7,61 – 7,67 and 7,63 – 7,79. DO 4,35ppm – 5,09ppm and 4,55ppm – 4,19ppm. Ammonia 0,01ppm and 0,01ppm – 0,1ppm